RFC1‐Related Disorder: In Vivo Evaluation of Spinal Cord Damage. Issue 10 (25th July 2022) - Rezende, Thiago J.R.; Schmitt, Gabriel S.; de Lima, Fabricio D.; de Brito, Mariana Rabelo; Matos, Paula Camila A.A.P.; Bonadia, Luciana Cardoso; Martinez, Alberto R.M.; Cendes, Fernando; Pedroso, José Luiz; Barsottini, Orlando G.P.; Marques, Wilson; França, Marcondes Cavalcante
Abstract: Background: RFC1‐related disorder is a novel heredodegenerative condition with a broad phenotypic spectrum. Its neuropathological bases are not yet fully understood, particularly regarding the pattern, extent, and clinical relevance of spinal cord (SC) damage. Objectives: The objectives were to determine the SC structural signature in RFC1‐related disorder in vivo and to identify potential clinical correlates for these imaging abnormalities. Methods: We enrolled 17 subjects with biallelic RFC1 (AAGGG)n expansions and 11 age‐ and sex‐matched healthy controls that underwent multimodal magnetic resonance imaging SC acquisitions in a 3T Philips Achieva scanner. Both global morphometry and tract‐specific analyses were then performed across all cervical levels. Between‐group comparisons were assessed using nonparametric tests. Results: In the patient group, mean age and disease duration were 62.9 ± 9.3 and 9.3 ± 4.0, respectively. Compared to controls, patients had remarkable SC cross‐sectional area reduction along all cervical levels but anteroposterior flattening only in the lower cervical levels. There was also prominent SC gray matter atrophy. Diffusivity abnormalities were identified in the dorsal columns but not in the lateral corticospinal tracts. Disease severity did not correlate with these imaging parameters. Conclusion: SC damage is a hallmark of RFC1‐related disorder and characterized by gray as well as white matter involvement. In particular, dorsal columns are severely and diffusely affected. The clinical correlates of these imaging abnormalities still deserve additional investigations. © 2022 International Parkinson and Movement Disorder Society.